The techniques of television interviewing - Minehan, Mike; Halliday, Eric; First Light Video Publishing; Australian Film, Television & Radio School; TMW Media Group, Inc. (Australia : AFTRS ; Venice, CA. : TMW Media Group, Inc. (distributor), 1986)
Presents television journalist Mike Minehan highlighting the ingredients of a dynamic and successful television interview. Uses excerpts that include examples of good technique as well as the pitfalls that await the unwary interviewer. Presents role models and cautionary tales
Title from title screen
Camera, George Petrykowski ; sound, John Dodds ; editor, Synthia Connop
Keywords: Interviewing on television; Talk shows; Television broadcasting of news